Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1080/26895269.2021.1964409
|View full text |Cite
|
Sign up to set email alerts
|

Experienced barriers of care within European treatment seeking transgender individuals: A multicenter ENIGI follow-up study

Abstract: Objectives: To evaluate the experienced barriers of care for treatment-seeking trans individuals (TSTG) in three large European clinics. Methods: An online follow-up questionnaire was filled out by 307 TSTG individuals as part of the research protocol of the European Network for the Investigation of Gender Incongruence (ENIGI). Data was collected during follow-up in 2017/2018, around 5 years after participants had their initial clinical appointments in Ghent (Belgium), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Transgender or trans people face significant challenges to accessing healthcare, encountering hurdles often unseen by cisgender people (Moseson et al., 2020 ; Ross et al., 2021 ; Strauss et al., 2021 ). Throughout trans sexual and reproductive health (SRH) care, sustained hetero-cis-normativity (Worthen, 2016 ), transphobia, and poor awareness and lack of training for health-workers often render crucial health services unapproachable (Gridley et al., 2016 ; Luvuno, Ncama, & Mchunu, 2019 ; Reisner et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Transgender or trans people face significant challenges to accessing healthcare, encountering hurdles often unseen by cisgender people (Moseson et al., 2020 ; Ross et al., 2021 ; Strauss et al., 2021 ). Throughout trans sexual and reproductive health (SRH) care, sustained hetero-cis-normativity (Worthen, 2016 ), transphobia, and poor awareness and lack of training for health-workers often render crucial health services unapproachable (Gridley et al., 2016 ; Luvuno, Ncama, & Mchunu, 2019 ; Reisner et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that cultural and societal values and norms may profoundly influence healthcare behaviour across these groups. Importantly, this dimension highlights the critical role of support and acceptance from family and peers in influencing healthcare access in twelve of the included studies [ 25 , 26 , 28 , 29 , 37 , 39 , 41 , 44 46 , 49 , 57 ].…”
Section: Results: Collating Summarizing and Reportingmentioning
confidence: 99%
“…In the context of healthcare seeking and reaching, availability and accommodation emerged as key factors, with the most prominent challenge being the identification of a provider or service that was willing to prescribe or treat (n = 19) [ 20 , 23 , 25 , 26 , 28 , 29 , 37 , 38 , 40 , 42 , 45 , 47 50 , 52 , 55 , 56 , 59 ]. Notably, a significant number of participants reported being denied care during the process of seeking healthcare (n = 12) [ 18 , 20 , 25 , 26 , 38 , 40 , 41 , 45 , 51 , 52 , 55 , 57 ], and persistent barriers to accessing care were associated with long waiting times (n = 8) [ 9 , 31 , 40 , 42 , 46 , 48 , 50 , 51 ]. One study explored homelessness as a factor impacting access to care [ 60 ].…”
Section: Results: Collating Summarizing and Reportingmentioning
confidence: 99%
“…In this study, the majority of participants reported various barriers, with the most frequently reported being the lack of support from the social environment, travel time to clinics and costs, and stiff treatment protocols in the sense that many participants reported they had to convince their provider they needed care and/or express their wish in such a way to increase their likelihood of receiving care. More mental health problems, lower income, and female gender were again associated with more negative experiences, suggesting that European health systems need to address both personal and systemic characteristics to overcome barriers to transgender care [ 102 ].…”
Section: Discussionmentioning
confidence: 99%